Myofibroblast secretome and its auto-/paracrine signaling. (3rd May 2016) - Bomb, Ritin; Heckle, Mark R.; Sun, Yao; Mancarella, Salvatore; Guntaka, Ramareddy V.; Gerling, Ivan C.; Weber, Karl T.
ABSTRACT: Myofibroblasts (myoFb) are phenotypically transformed, contractile fibroblast-like cells expressing α-smooth muscle actin microfilaments. They are integral to collagen fibrillogenesis with scar tissue formation at sites of repair irrespective of the etiologic origins of injury or tissue involved. MyoFb can persist long after healing is complete, where their ongoing turnover of collagen accounts for a progressive structural remodeling of an organ (a.k.a. fibrosis, sclerosis or cirrhosis). Such persistent metabolic activity is derived from a secretome consisting of requisite components in the de novo generation of angiotensin (Ang) II. Autocrine and paracrine signaling induced by tissue AngII is expressed via AT1 receptor ligand binding to respectively promote: i ) regulation of myoFb collagen synthesis via the fibrogenic cytokine TGF-β1 -Smad pathway; and ii ) dedifferentiation and protein degradation of atrophic myocytes immobilized and ensnared by fibrillar collagen at sites of scarring. Several cardioprotective strategies in the prevention of fibrosis and involving myofibroblasts are considered. They include: inducing myoFb apoptosis through inactivation of antiapoptotic proteins; AT1 receptor antagonist to interfere with auto-/paracrine myoFb signaling or to induce counterregulatory expression of ACE2; and attacking the AngII-AT1 R-TGF-β1 -Smad pathway by antibody or the use of triplex-forming oligonucleotides.